2007
DOI: 10.3168/jds.2006-803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bifidobacterium bifidum Fermented Milk on Helicobacter pylori and Serum Pepsinogen Levels in Humans

Abstract: Helicobacter pylori infection is an important risk factor for gastric diseases. Some probiotics are useful for suppressing H. pylori infection. Bifidobacterium bifidum YIT 4007 can improve the experimental gastric injury in rats and the disease stages on the gastric mucosa in peptic ulcer patients. We evaluated the fermented milk using a clone (BF-1) having the stronger ability to survive in the product than this parent strain to clarify the in vitro suppressive effect of BF-1 on H. pylori and the in vivo effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 51 publications
1
43
1
Order By: Relevance
“…Furthermore, in clinical trials with human volunteers, the incidence of gastrointestinal disorders declined after ingestion of lactobacilli, and in some cases, H. pylori levels decreased, although H. pylori infection was hardly ever fully eradicated (3). With respect to Bifidobacterium, Miki et al (35) reported that ingestion of B. bifidum in fermented milk by H. pylori-positive subjects affected their urea breath test values, serum pepsinogen levels, and upper gastrointestinal symptoms. The aforementioned results indicate that even though positive results have been obtained with probiotics pertaining to the genus Lactobacillus, few studies have focused on Bifidobacterium activity against H. pylori.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in clinical trials with human volunteers, the incidence of gastrointestinal disorders declined after ingestion of lactobacilli, and in some cases, H. pylori levels decreased, although H. pylori infection was hardly ever fully eradicated (3). With respect to Bifidobacterium, Miki et al (35) reported that ingestion of B. bifidum in fermented milk by H. pylori-positive subjects affected their urea breath test values, serum pepsinogen levels, and upper gastrointestinal symptoms. The aforementioned results indicate that even though positive results have been obtained with probiotics pertaining to the genus Lactobacillus, few studies have focused on Bifidobacterium activity against H. pylori.…”
mentioning
confidence: 99%
“…Lactobacillus acidophilus (2,3,30), Lactobacillus casei strain Shirota (46), Bacillus subtilis (42), and even Weissella confusa (38) have rendered an antagonistic effect against the bacterium. Some in vitro studies showing bifidobacterial activity against H. pylori have been reported, with different levels of success (34,35), but they remain scarce. Regarding the metabolites involved in growth inhibition, lactic acid and other organic acids are con-sidered to play a major role (2,35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bifidobacterium bifidum strain YIT 10347 (BF-1) was isolated from B. bifidum YIT 4007 as an oxygen-resistant strain, and it is used as a starter culture for the production of fermented milk products. The consumption of fermented milk containing BF-1 can improve gastric symptoms caused by Helicobacter pylori infection (5), and BF-1 affects regulatory mechanisms in human cells, especially nuclear factor kappa B (NF-B) expression, which is induced by H. pylori infection (6).…”
mentioning
confidence: 99%
“…Therefore, in order to both, reduce antibiotic side effects and improve patient compliance, there is a clear need for the development of new treatment approaches, replacing antibiotics. Recent reports show that natural phytochemicals in combination with lactic acid or lactate are promising alternatives to antibiotics (Pantoflickova et al, 2003;Miki et al, 2007;Apostolidis et al, 2011;Michael et al, 2011;Lin et al, 2011;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%